Madīnat al-Zahrā‘, Spain. A Pottery Ensemble from the »Patio de los Pilares«. Research Carried Out between March 2019 and February 2020 - Martín García, Alejandro I. (e-Forschungsberichte des DAI, 2023)
Madīnat al-Zahrā’ is an archaeological site located near the city of Córdoba (Spain), barely 7 km away, founded in 940 CE by Caliph ’Abd al-Rahmān III, a few years after the proclamation of the caliphate. This place is extremely important due to its status as a palatine city until 1010 CE, the year that marks its end and destruction as a result of the fitna, the civil war that took place in al-Andalus. This research focuses on the study of pottery in the space known as »Patio de los Pilares«, a place that presents different questions about its function and phases. This material was found in an enclosed area within a reliable stratigraphy, so one of the main objectives is to present a chronology that is as clearly defined as possible in order to serve as a reference in the future. A large part of the material corresponds to a waste context, which is interesting as it allows us to get closer to more daily aspects of the archaeological site, especially service tasks.